2018
DOI: 10.1186/s40066-018-0209-x
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts and adaptation among smallholder farmers in Central America

Abstract: Background: Smallholder farmers are one of the most vulnerable groups to climate change, yet efforts to support farmer adaptation are hindered by the lack of information on how they are experiencing and responding to climate change. More information is needed on how different types of smallholder farmers vary in their perceptions and responses to climate change, and how to tailor adaptation programs to different smallholder farmer contexts. We surveyed 860 smallholder coffee and basic grain (maize/bean) farmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
151
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(171 citation statements)
references
References 56 publications
(96 reference statements)
10
151
0
10
Order By: Relevance
“…Addressing these shortcomings is important for supporting smallholders to overcome global risks of extreme weather events, natural disasters, and failures of climate change mitigation and adaptation [98]. Our analysis has identified key recommendations that will serve as a valuable guide for the success of future AGI developments whereby knowledge gaps and implementation challenges should be addressed, particularly to align with the geographically varying needs of smallholder farmers (e.g., [99,100]. Use of AGI initiatives could greatly aid smallholders to move towards climate-smart agriculture [101] for sustainably increasing productivity [44], improving environmental livelihood security [102], and enhancing landscape resilience under a changing climate [103].…”
Section: Discussionmentioning
confidence: 99%
“…Addressing these shortcomings is important for supporting smallholders to overcome global risks of extreme weather events, natural disasters, and failures of climate change mitigation and adaptation [98]. Our analysis has identified key recommendations that will serve as a valuable guide for the success of future AGI developments whereby knowledge gaps and implementation challenges should be addressed, particularly to align with the geographically varying needs of smallholder farmers (e.g., [99,100]. Use of AGI initiatives could greatly aid smallholders to move towards climate-smart agriculture [101] for sustainably increasing productivity [44], improving environmental livelihood security [102], and enhancing landscape resilience under a changing climate [103].…”
Section: Discussionmentioning
confidence: 99%
“…Highly variable precipitation is among the many challenges faced by the millions of families who rely directly on smallholder farming in Central America (PRESANCA-FAO 2011, Van der Zee Arias et al 2012) and is linked to both food insecurity and migration (Lobell et al 2008, Nawrotzki et al 2016. Recently, smallholder farmers have reported changes in the distribution and intensity of rainfall across Central America, resulting in crop losses and reductions in yields for those already contending with pervasive social and economic inequalities (Eakin et al 2014, Pons et al 2016, Hellin et al 2017, de Sousa et al 2018, Harvey et al 2018, Rice 2018, Bellante 2019. Farmers in the western highlands of Guatemala and the Chiapas lowlands of Mexico have specifically reported that the Central American Midsummer Drought (MSD) (Magaña et al 1999) is becoming more prolonged, increasingly variable, and harder to predict (Hellin et al 2017, Bellante 2019.…”
Section: Introductionmentioning
confidence: 99%
“…A maioria desses estudos concentrou-se nas principais commodities, como café, milho, arroz, batata, trigo, cana-de-açúcar e soja. Poucos estudos se concentraram na produção de frutas, que é uma importante fonte de renda dos agricultores familiares e pequenos produtores no mundo, e onde esses impactos podem ser particularmente graves devido à alta vulnerabilidade desses agricultores (Donatti et al, 2018;Holland et al al., 2017;Harvey et al, 2018) Os pequenos agricultores (ou agricultores familiares) desempenham um papel importante no sistema agrícola e na segurança alimentar mundial (FAO, 2014).…”
Section: Introductionunclassified